Technological moisture as a cause of moulds on building partitions = Wilgoć technologiczna przyczyną występowania grzybów pleśniowych na przegrodach budowlanych - Piontek, Marlena; Łuszczyńska, Katarzyna; Lechów, Hanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The intense pace of construction work means that technical materials contain so-called technological moisture, which enables the development of biodeteriogenic organisms on building partitions. This article presents the mycological analysis of two buildings in Zielona Góra, whose building partitions were affected by colour deposits.
Keywords: technological moisture; biodeterioration; moulds; mould in the building; wilgoć technologiczna; biodeterioracja; grzyby pleśniowe; pleśń w budynku